Management accounting a strategic approach - Morse, Wayne J. (South-Western College Pub., 1996)
Specially designed for your managerial accounting course if you place emphasis on relating management accounting to other subject areas. The text thoroughly integrates issues that have emerged during the past ten years. By taking a value chain approach and stressing management accounting as an employee and management empowerment tool, this text is relevant, interesting, and usable for students whose primary concerns are something other than financial reporting. Easily covered in one semester.